(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article analyzes the impact of various types of defects on yarns. The formation of thickened yarns due to sliver breakage in natural and synthetic fibers is discussed. Such defects mainly result from improper reconnection of the sliver after it breaks. The study investigates the causes of these breakages and evaluates preventive measures aimed at reducing their occurrence. The results provide insights into improving yarn quality by minimizing sliver breakage through optimized mechanical adjustments and process control.